Autopolyploidy‐driven range expansion of a temperate‐originated plant to pan‐tropic under global change. Issue 2 (2nd February 2021) - Cheng, Jiliang; Li, Jun; Zhang, Zheng; Lu, Huan; Chen, Guoqi; Yao, Beibei; Dong, Yingxue; Ma, Ling; Yuan, Xiaoxiao; Xu, Jingxuan; Zhang, Ying; Dai, Weimin; et al.
Abstract: Angiosperms are believed to have emerged initially in the tropics and expanded their distribution range poleward through diverse mechanisms, for example polyploidization‐driven cold tolerance evolution. Reversed expansion from temperate to pan‐tropic climates through a polyploidization‐driven shift in heat tolerance remains largely unknown. Here, we found autopolyploidy in relation to the global expansion of Solidago canadensis from its temperate‐climate native range in North American to hot‐summer climate in an introduced range. Our cytogeographical study of 2, 062 accessions from 471 locations worldwide demonstrates that ploidy levels correlate negatively with latitude and positively with average temperature. An isotherm‐dependent shift of the climate niches at the threshold of 20°–24°C between geo‐cytotypes can be attributed mainly to autopolyploidy‐driven differentiation of heat tolerance; only polyploids and not diploids are able to complete sexual reproduction, germinate, and grow in the hot‐summer climate of low latitudes. Ploidy‐dependent fertility appears to play a key role in the hot‐summer introduced range in the northern hemisphere through both pre‐adaptation and rapid post‐introduction adaptive evolution of delayed flowering and improved heat tolerance during embryo development. The MaxEnt model predicts continued expansion of this plant species under global change. These results provide new insights into the mechanisms governing autopolyploidy‐driven backward range expansion of plant species from temperate origins.